Implementação das boas práticas na atenção ao parto em maternidade de referência - Bruna Marques de Melo; Linicarla Fabiole de Souza Gomes; Ana Ciléia Pinto Teixeira Henriques; Sâmua Kelen Mendes de Lima; Ana Kelve de Castro Damasceno (Universidade Federal do Ceará, 2017)
Objective : to describe the implementation of good practices of attention to labor at a reference maternity. Methods : descriptive, documentary study, with 300 Forms for Monitoring Assistance to Labor and Birth. The data were gathered on tables and submitted to descriptive and numerical inferential analysis. Results : in category A we observed that 48.3% of the births filled the partogram; 84.0% of women did not use pharmacological methods for pain relief; 67.0% remained at zero diet during labor; 84.7% had no companion during labor, delivery and after giving birth; 57.0% had skin-to-skin contact; and 65.3% breast-fed in the delivery room. In category B it was found that 54.0% of women remained in venoclysis; 60.7% remained in semi-sit position in the expulsive period; and 14.7% women were shaved. Conclusion : some practices proved useful in childbirth are still not implemented in many cases, while others that are harmful or ineffective are still being carried out.